Economic and Environmental Effects from Liberalizing Utility Service Prices in the Republic of Serbia - Radukic, Snezana; Perovic, Dusan; Vucetic, Dejan (Industrija, 2018)
The aim of research is to determine what kind of effects would price liberalization in public utility sector produce on inflation, standard of living and air quality in the Republic of Serbia. For the purpose of analysis financial reports of public utility companies were used including population number of 14 Serbian cities that were part of research, share of utility prices in consumption price index (CPI) and air quality statistics for analysed cities. The analysis covers period of 2008 – 2016 when significant changes in the operations of Serbian public utility companies occurred. Since all public utility companies receive the subsides from state and local authorities and most of them achieve loss in their reports, analysis will show economic and environmental effects from possible switch of public utility companies to market – based surroundings. This will help in determining the role of public utility companies in achieving sustainable development concept, which is important for creating future sustainable activities of public utility companies in the Republic of Serbia.
Keywords: inflation; standard of living; air quality; sustainability; Utility; Liberalism